Characterization of a Sub-Atmospheric Pressure-Inducing Micropump Based on Flow Rate and Gauge Pressure Measurements - William L. N, Buglie; Khairul Fikri, Tamrin (John Wiley & Sons, Inc., 2023)
The pumping mechanism in multi-inlet microfluidic channels usually requires multiple micropumps to be separately attached to each inlet. Unfortunately, this may create fluid leakage resulting from a considerably high internal pressure. To address this, a passive sub-atmospheric pressure-inducing micropump is proposed and its performance is characterized as a function of the flow rate and the gauge pressure. With this pump, a sufficiently high flow rate is generated, comparable to some active-piezoelectric micropumps. The gauge pressure is exponentially descending with time and can be crudely classified into three regions of high, moderate, and slow pressure-release times. Overall, the stabilized pressure is identified within 70 s < t £ 300 s for slow rate mixing while rapid mixing is applicable at t £ 70 s.